Partnership between Government of Kenya and the International Livestock Research Institute's Mazingira Centre for livestock productivity and mitigating emissions - Arndt, Claudia; Kimoro, Bernard (CGIAR System Organization, 2024)
"Reducing greenhouse gas (GHG) emissions from livestock systems is a priority of the Livestock and Climate Initiative. Working with the CGIAR Research Initiative on Low Emission Food Systems, the Livestock and Climate Initiative has established a strong partnership with the State Department for Livestock Development (SDLD) within the Ministry of Agriculture and Livestock Development through the Mazingira Centre hosted by the International Livestock Research Institute (ILRI). This successful collaboration is focused on the interlinked goals of increasing livestock productivity as part of national food and nutrition security initiatives while also identifying climate-smart agriculture practices for livestock production that help reduce emissions per product. The partnership has led to Kenya publishing more accurate data for measurement, reporting, and verification of GHG emissions from the livestock sector and collaborative science on developing technical interventions focused on mitigation and support for livestock sector policy."